Incidence, course and risk factors of head injury: a retrospective cohort study. Issue 5 (31st May 2018) - Gerritsen, Herman; Samim, Mariam; Peters, Hans; Schers, Henk; Laar, Floris van de
Abstract : Objectives: To assess the incidence of head injury and predictors of complication across the care continuum. Design: Retrospective cohort study using data from a research network. We calculated the incidence of overall head injury in a longitudinal cohort covering 1-year interval (31 369 patient-years), and the incidence of complicated head injury in a longitudinal cohort covering 10 years interval (220 352 patient-ears). Incidence rates were calculated per 1000 patient-years with 95% CI using the Mid-P exact test. We calculated ORs to assess potential risk factors for a complicated head injury. Setting: A practice-based research network covering a population of >30 000 patients. Participants: All patients listed in practices within the research network during the years 2005–2014. Main outcome measures: Incidence of (complicated) head injury and predictors for clinical complications. Results: The incidence of overall head injury was 22.1 per 1000 person-years and the incidence of a complicated course following head injury was 0.16 per 1000 person-years. The following determinants were risk factors for a complicated course: high energy trauma, bicycle accident, traffic accident in general, use of anticoagulants, alcohol intoxication, age above 60 years and low Glasgow Coma Scale at initial presentation. A complicated course was very unlikely when the patients' first encounter with a healthcare professional was in primary care (OR 0.03, 95% CI 0.01 to 0.07). Conclusions: Complication after head injury are rarely seen in general practice. Patients who do experience complications are often easily identifiable as requiring specialist care. A more reserved referral policy for general practice may be desirable, suggesting that current guidelines are too defensive.